Pharmacological preconditioning with the adenosine triphosphate–sensitive potassium channel opener pinacidil - Saltman, Adam E; Krukenkamp, Irvin B; Gaudette, Glenn R; Horimoto, Hitoshi; Levitsky, Sidney (The Annals of thoracic surgery, 2000)
Background. Ischemic preconditioning (IPC) decreases infarct size after global or regional ischemia. Potassium channel openers also precondition but are subject to dose-limiting vasodilation. We compared the mechanical and electrophysiological effects of ischemic and pharmacological preconditioning in an isolated rabbit heart model. Methods. Rabbit hearts were preconditioned with either 10 μmol/L pinacidil alone (P−), 10 μmol/L pinacidil with 10 μmol/L phenylephrine (P+), or two cycles of global ischemia and reperfusion (IPC) before 1 hour of LAD occlusion. Left ventricular pressure, epicardial monophasic action potential duration (APD) and coronary flow were monitored throughout. Infarct size was determined at the end of reperfusion. Results. Regional ischemia uniformly decreased APD ( p < 0.05). During reperfusion, APDs were prolonged beyond preischemic values in all preconditioned groups ( p < 0.05). P− and P+ reduced the incidence of fibrillation. P− significantly increased coronary flow (+15%, p = 0.001), whereas IPC and P+ did not. However, IPC and P− significantly decreased systolic function ( p < 0.05) but P+ did not. In addition, IPC depressed diastolic function ( p < 0.05) but P− and P+ did not. Infarct size was reduced by all methods ( p < 0.05). Conclusions. Pinacidil presents a safe and effective alternative to IPC for preserving the heart during regional ischemia. Its coronary vasodilatory effects are safely and effectively reversed by the addition of phenylephrine.